Researcher's personal diary as research tool (2010)
This document is based on the revision of personal diaries of interviewers who are part of a research team in the South of Florida, United States. The original study explored the patterns of care provided to elderly people at home. The reflecting personal diaries stimulated a broaden discussion on the researched topic, presented the human aspect of quantitative data and, given the sensible character of the topic under study, served the researchers to identify and explore their own emotions prior to meeting the participants of the study. Our experience confirms the need to use qualitative mythological instruments that help reveal the phenomenon under research "just as it occurs", through complementing the quantitative evidence. The argument is that having an open and self-reflective attitude, in the middle of the current enthusiasm for practice based on evidence, is not only applicable in the framework of nursing research but within the same professional practice.